Education On Balanced Nutrition As A Prevention Of Hidden Hunger For Female Adolescent - Amanda Zsa-Zsa Paramita; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study is to educate the female adolescent regarding balanced undernourishment causes hidden hunger. The method research that will used is descriptive quantitative to 32 students at Daarul Haliim Boarding School. Study conducted through 3 stages: (1) pre-test, (2) giving education, and (3) post-test. The results showed that the pretest score was 0.018 and the posttest score was 0.036. The pre-test average result was 40.00 and post-test average result was 87.50. The results of the Wilcoxon test is 0.000α=0.05. From these results, we can conclude education about balanced nutrition as a prevention take effect significant to understanding female adolescent as effort to prevention of hidden hunger. This is because (1) the education was interactive, (2) research subjects enthusiastic during the education, and (3) the educational media very interesting. With the completion of this research, it is hoped more female adolescents will understands nutrition balanced as prevention happening of hidden hunger.